2015
DOI: 10.1515/amcs-2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and combinatorial algorithms for optimal sizing and placement of active power filters

Abstract: The paper deals with cost effective compensator placement and sizing. It becomes one of the most important problems in contemporary electrical networks, in which voltage and current waveform distortions increase year-by-year reaching or even exceeding limit values. The suppression of distortions could be carried out by means of three types of compensators, i.e., passive filters, active power filters and hybrid filters. So far, passive filters have been more popular mainly because of economic reasons, but activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It has been shown that the case of leaving harmonics in the network at the level permitted by the standards is 40% cheaper than the case of full harmonic reduction, and the economically optimal variant is even 60% cheaper (in this case, the THDV factor was reduced by almost a half in the supply network). A comparison of the efficiency of this method with the results obtained with the use of the genetic algorithm can be found in [128]. The case of minimum cost may lead to a solution involving the connection of more APFs but less power.…”
Section: Classic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the case of leaving harmonics in the network at the level permitted by the standards is 40% cheaper than the case of full harmonic reduction, and the economically optimal variant is even 60% cheaper (in this case, the THDV factor was reduced by almost a half in the supply network). A comparison of the efficiency of this method with the results obtained with the use of the genetic algorithm can be found in [128]. The case of minimum cost may lead to a solution involving the connection of more APFs but less power.…”
Section: Classic Methodsmentioning
confidence: 99%
“…In most cases, the authors do not specify which tools they used, but it can be assumed that it was software designed to solve a specific problem. In some articles [112][113][114][115]117,123,[126][127][128][131][132][133]137,138,141,143,146,149], the authors stated that they used a universal tool such as Matlab (MathWorks, Natick, MA, USA). To analyze the flow of higher harmonics, the ATP (EEUG e.V., Kiel, Germany) [137], EATP (ETAP-Operation Technology, Irvine, CA, USA) [113], and PCFLO [111,126,127,132,133,138] were also used.…”
Section: Test Systems and Software Solutionsmentioning
confidence: 99%
“…The solution to basic problem (1) as well as to its modifications for different APF control algorithms and constraints has been presented in [34][35][36][37][38]. The main constraints taken into account include:…”
Section: Sizing and Placement Of Apfs In Power Networkmentioning
confidence: 99%
“…It could be run in the batch mode using the command line instructions and reading all the configuration options as well as input data from text files prepared by the user. Matlab software, supported by a few classes written in JAVA and used to PCFLO file handling [18], has been chosen as an upper level application controlling the whole optimization process. The block diagram of the proposed optimization software system has been presented in Fig.…”
Section: Software System For Optimization Of Compensation Costsmentioning
confidence: 99%
“…• development of a goal function based on real costs of active compensation so that optimization results reflected the investment costs in the best possible way, • development of complete optimization algorithms leading to such allocation of compensation devices in large supply systems that allows to put the assumed goals, reflected by the proposed or any other goal function, into practice [18], • development of a software package which enables harmonic flow analysis and application of arbitrary optimization methods for allocation of active compensators including hybrid ones, • analysis of compensation costs in a large supply system including almost 450 buses.…”
Section: Introductionmentioning
confidence: 99%